Adaptation and Validation of the Abusive Supervision Scale: A Short Version for the Indonesian Context - Rizky Nur Fahrezi; Hillman Wirawan; Findra Anugrah Putri Firdaus; Zahra Rizqi Quraini M. Zulkifli; Uswatun Hasanah Nurkholis; Asma (International Journal of Educational Administration, Management, and Leadership, 2026)
This study aims to adapt and examine the construct validity and internal reliability of the Abusive Supervision Scale Short Version (5-item) in the Indonesian context. The background of this research is based on the limited number of studies on abusive supervision in non-Western countries, particularly in Indonesia, which is characterized by high power distance. This study employed a quantitative approach with a cross-sectional survey design involving 252 employees who have direct supervisors in the province of South Sulawesi. The sample was selected purposively, and the scale was administered via an online platform. Data analysis was carried out using Confirmatory Factor Analysis (CFA) with the WLSMV estimation method. The results show that the unidimensional model of the scale has a very good fit based on CFI (.998), TLI (.996), and SRMR (.019), with an RMSEA value of (.099). All items had factor loading values above 0.89 and were significant (p < .001), as well as an Average Variance Extracted (AVE) value of .89. In addition, the overall Omega coefficient value of .94 indicates very high internal reliability. These findings indicate that this scale is proven to be valid and reliable in measuring perceptions of abusive supervision in the Indonesian context. Practically, this short scale is useful for researchers and organizational practitioners because it can be used efficiently without increasing respondent fatigue, while still being able to provide an accurate depiction of the dynamics of abusive supervision.